OPERATIONAL STRATEGY TO IMPROVE ANALYST PERFORMANCE AT JAKARTA IT SERVICE DESK OF ROYAL BLUE ENERGY - Kamilla Sukmahati; Yudo Anggoro (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Global Service Desk operates 24/7 and covers the entire Royal Blue Company work area in the world, utilizes a ticketing system to handle IT service issues and requests. This study focused on the Jakarta Service Desk (JSD) and analyzed operational performance from January to June 2025. The study aimed to examine the strategies implemented within the JSD and the challenges faced in improving the work performance of each analyst. In a dynamic work environment, increasing ticket volumes, and continuous technological advancements, JSD analysts are expected to survive by achieve the targeted performance. The implemented strategies included weekly training programs conducted by the service excellence team, a self-service portal for users, automation tools (RTBot), shift-left initiatives, weekly role rotation, and more. The analysis used Gap Analysis and the Fishbone Analysis. By identifying gaps in each aspect that impact analyst performance and determining the root cause of the problem, analysts are expected to focus on narrowing the gaps and working on root cause so that results can meet the set targets. The results show that the critical gap in this research is with the Live Interactions per Shift. If this critical gap fixed, this would take effect to others performance like chat & call answer. These findings tell us that the collaboration from each analyst in this desk is required to achieve targets according to KPIs and provide satisfactory service to each user.